Understanding the prolonged impact of online sexual abuse occurring in childhood - Schmidt, Felipa; Varese, Filippo; Bucci, Sandra (Frontiers in Psychology, 2023)
Introduction There has been a rapid increase in prevalence rates of online sexual abuse (OSA). Existing research has highlighted the negative impact OSA can have on victims. However, there is a gap in understanding the long-term impact of OSA when it occurred in childhood. Methods This qualitative study comprised interviews with eight female participants aged 18–28 years recruited in UK NHS Trusts, and via mental health charities, University bulletins and social media. Each participant self-reported having experienced abuse through either the production or dissemination of sexual material online. Results Results showed that the longer-term impact of OSA was multi-fold, including negative impact on sense of self and broader interpersonal relationships, and significant impact on the participants’ mental health, including experiences of self-harm, anxiety, and low mood. Likewise, participants discussed long-term apprehension to taking images and the added fear and worry that their sexual images were distributed online. Seven participants had received mental health support but only two recounted a positive experience when receiving support for OSA. Discussion Future research using a quantitative longitudinal design is needed to further explore the prolonged impact of OSA. Clinical implications of the research highlight the need for support services to assess the impact of OSA and interventions that target OSA experiences.